Pengaruh Pemberian Pupuk Gambut dan Urea terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Pada Pembibitan Pre-Nursery - Mohammad Hertos (Anterior Jurnal, 2014)
The purpose of this research was to find Pugam T and Urea interactions on the growth for Oil Palm in Pre Nursery to Peat Soil. The research was arranged in Completely Randomised with two factors and three duplications. This first factor was to find Pugam T (P) on four levels: 0 kg/ha (P0), 750 kg/ha (P1), 1000 kg/ha (P2) and 1.250 kg/ha (P3), the second factor was Urea (N) on four levels: 0 g/l (N0), 1 g/l (N1), 2 g/l (N2) and 3 g/l (N3). The results show the experiment of treatments Pugam T and Urea was significantly on the parameters: plant height, the stem of diameters, weight fresh of plant and root lengths of primers. The heighest yield to parameters of plant height in old 4,8 and 12 MST (10,57 cm, 31,03 cm and 35,00 cm), stem of diameters in old 4,8 and 12 MST (0,57 cm, 0,66 cm and 0,90 cm), weight fresh of plant (16,8 g) and root lengths of primers (26,08 cm). Obtainable on the treatments to find Pugam T as big as 1.250 kg/ha and Urea as big as 3 g/l (P3N3).